Easy albumin–bilirubin score as a new prognostic predictor in hepatocellular carcinoma. Issue 11 (5th June 2021) - Ho, Shu‐Yein; Liu, Po‐Hong; Hsu, Chia‐Yang; Ko, Chih‐Chieh; Huang, Yi‐Hsiang; Su, Chien‐Wei; Hsia, Cheng‐Yuan; Tsai, Ping‐Hsing; Chou, Shih‐Jie; Lee, Rheun‐Chuan; Hou, Ming‐Chih; Huo, Teh‐Ia
Abstract: Background: Liver functional reserve is a major prognostic determinant in patients with hepatocellular carcinoma (HCC). The albumin–bilirubin (ALBI) score is an objective method to assess the severity of cirrhosis in this setting. However, calculation of the ALBI score is complex and difficult to access in clinical practice. Recently, the EZ (easy)‐ALBI score was proposed as an alternative biomarker of liver injury. We aimed to evaluate the prognostic role of the EZ‐ALBI score in HCC from early to advanced stages. Methods: A total of 3794 newly diagnosed HCC patients were prospectively enrolled and retrospectively analyzed. Independent prognostic predictors were determined by using the multivariate Cox proportional hazards model. Results: The EZ‐ALBI score showed good correlation with the ALBI score (correlation coefficient, 0.965; p < 0.001). The correlation of the EZ‐ALBI score was highly preserved in different Child–Turcotte–Pugh (CTP) classifications, treatment methods, and Barcelona Clinic Liver Cancer (BCLC) stages (correlation coefficients, 0.90–0.97). In the Cox multivariate analysis, age >65 years, male sex, serum α ‐fetoprotein >20 ng/ml, large or multiple tumors, total tumor volume >100 cm 3, vascular invasion or distant metastasis, ascites, poor performance status, EZ‐ALBI grade 2 and 3, and noncurative treatments were independently associated with increased mortality (all p < 0.05). Moreover, EZ‐ALBI grade can stratify long‐term survival in patients with different CTP class, treatment strategy, and BCLC stage. Conclusions: The EZ‐ALBI score is an easy and feasible method to evaluate liver functional reserve. As a new prognostic biomarker in HCC, the predictive power of the EZ‐ALBI grade is independent across different cancer stages and treatments.